Peran Badan Usaha Milik Desa (Bumdes) Lestari Jaya Dalam Meningkatkan Aktivitas Ekonomi Kerakyatan Di Kampung Walal Perspektif Ekonomi Islam - Widas Widas (Prodi Ekonomi Syariah IAIN Sorong, 2021)
The Village-Owned Enterprise (BUMDES) Lestari Jaya was established on January 15, 2016. At that time this BUMDES was first established in the Sorong Regency, precisely in Walal Village, Salawati District, Sorong Regency, West Papua. At that time, BUMDES Lestari Jaya had not yet developed and was still in the capital search stage for the formation of business units that are currently being run. The method used in this research is descriptive qualitative. Sources of data used are primary and secondary data. Then the data obtained from the results of observations, interviews, questionnaires, and documentation. With the population managing BUMDES Lestari Jaya, Village Government Officials, and the community totaling 10 respondents. The results of the study revealed that the role of BUMDES Lestari Jaya in Improving People's Economic Activities This Islamic Economic Perspective has a very positive impact on the people of Kampung Walal. This can be seen from the increase in community activities in their economic activities such as agricultural activities, trade and savings and loans provided by BUMDES Lestari Jaya. Besides that, BUMDES is also able to provide Village Original Income (PAD). To carry out all activities in the walal village in accordance with sharia principles without any coercion and burdening any party.